OP0309-HPR Knee Joint Stabilization Therapy in Patients with Osteoarthritis of the Knee: A Randomized, Controlled Trial. (23rd January 2014) - Knoop, J.; Dekker, J.; van der Leeden, M.; van der Esch, M.; Thorstensson, C. A.; Gerritsen, M.; Voorneman, R. E.; Peter, W. F.; de Rooij, M.; Romviel, S.; Lems, W. F.; Roorda, L. D.; et al.
Abstract : Background: Exercise therapy is a cornerstone treatment in knee OA, but effects on pain and activity limitations are only moderate at best. Objectives: To test our hypothesis that an exercise program, initially focusing on knee joint stabilization and subsequently on muscle strength and performance of daily activities is more effective in reducing activity limitations in patients with knee osteoarthritis (OA) and instability of the knee joint, compared to an exercise program focusing on muscle strength and performance of daily activities only. Methods: A single-blind, randomized, controlled trial involving 159 knee OA patients with self-reported and/or biomechanically assessed knee instability, randomly assigned to two treatment groups. Both groups received a supervised exercise program for 12 weeks, consisting of muscle strengthening exercises and training of daily activities, but only in the experimental group exercises initial knee stabilization training was provided. Outcome measures included activity limitations (WOMAC physical function, primary outcome), pain, global perceived effect and knee stability. Results: Both treatment groups demonstrated large ( 20-40%) and clinically relevant reductions in activity limitations, pain and knee instability, which were sustained six months post treatment. No differences in effectiveness between experimental and control treatment were found on WOMAC physical function (B (95% CI) = -0.01 (-2.58-2.57)) or secondary outcome measures, except for a higher global perceived effect in the experimental group (p=.04). Subgroupanalyses revealed a significant interaction between baseline upper leg muscles strength and group effect on WOMAC, physical function (p=.02). Conclusions: Both exercise programs were highly effective in reducing activity limitations and pain and restoring knee stability. Addition of specific knee joint stabilization training does not seem to be necesarry in the targeted group of knee OA patients suffering from knee instability, although subgroupanalyses suggest that those persons that have stronger upper leg muscles at baseline may benefit more from an exercise program that additionally focuses on knee joint stabilization. Disclosure of Interest: None Declared